1991
DOI: 10.1002/j.1551-8833.1991.tb07199.x
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Potable Water by Permeation of Plastic Pipe

Abstract: Sites of seven incidents of plastic pipe permeation were visited between July 1986 and December 1987, and samples of soil, pipe material, and pipe water were collected. In addition, a comprehensive literature review was undertaken to document other cases of permeation. This work demonstrated that the majority of permeation incidents were associated with gross soil contamination in the area surrounding the pipe. Soil contamination occurred mainly after pipe installation, suggesting that soil analysis prior to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 1 publication
2
38
0
Order By: Relevance
“…Toluene and xylenes were the major compounds detected in the pipe water, whereas the permeation of benzene through pipes was insignificant. These observations were consistent with results reported from other permeation incidents (Holsen et al, 1991a). In three reported incidents involving gasoline, toluene permeated to the greatest degree, followed by xylenes, ethylbenzene, and benzene (in the same order as shown in Figure 5, part A), whereas in the other cases associated with gasoline, xylenes permeated more readily, followed by toluene and ethylbenzene (in the same order shown in Figure 5, parts B and C).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Toluene and xylenes were the major compounds detected in the pipe water, whereas the permeation of benzene through pipes was insignificant. These observations were consistent with results reported from other permeation incidents (Holsen et al, 1991a). In three reported incidents involving gasoline, toluene permeated to the greatest degree, followed by xylenes, ethylbenzene, and benzene (in the same order as shown in Figure 5, part A), whereas in the other cases associated with gasoline, xylenes permeated more readily, followed by toluene and ethylbenzene (in the same order shown in Figure 5, parts B and C).…”
Section: Resultssupporting
confidence: 93%
“…The higher susceptibility of small‐size pipes to permeation is supported by the findings of a study of real permeation incidents that reported all permeation incidents for service lines were associated with pipe ≤ 1 in. in diameter (Holsen et al, 1991a). For the same bulk concentration, the concentration of contaminant in pipe water decreases with increasing pipe size, mainly because of the increase of wall thickness and the resulting decrease in permeation rate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical interaction is very important to potable water pipe stakeholders because it can impact water safety, aesthetics, and structural integrity. Chemical interaction can be examined by immersing polymer samples in neat contaminant solution [67][68][69] or by exposing them to dilute aqueous solutions [70][71][72][73]. Most accelerated ageing techniques [7,9,11,14,16,17,22,25,43] Source: Dietrich and WheltonÓ2008 Awwa Research Foundation.…”
Section: Introductionmentioning
confidence: 99%